Serum HDL-cholesterol in women using low dose oral contraceptives - Nessa, A; Latif, SA; Uddin, MM; Hussain, MA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S3-6The abstract of this article is available on the PubMed website